Hypoxia-Induced LIN28A mRNA Promotes the Metastasis of Colon Cancer in a Protein-Coding-Independent Manner - Weng, Mingjiao; Feng, Yukuan; He, Yan; Yang, Weiwei; Li, Jing; Zhu, Yuanyuan; Wang, Tianzhen; Wang, Chuhan; Zhang, Xiao; Qiao, Yu; Li, Qi; Zhao, Lingyu; et al. (Frontiers in Cell and Developmental Biology, 2021)
The hypoxic microenvironment is beneficial to the metastasis but not to the proliferation of cancer cells. However, the mechanisms regarding to hypoxia differentially regulating cancer metastasis and proliferation are largely unknown. In this study, we revealed that hypoxia induced the expression of LIN28A at mRNA level but segregated LIN28A mRNAs in the P-bodies and thus inhibits the production of LIN28A protein. This unexpected finding suggests that there may be non-coding role for LIN28A mRNA in the progression of colon cancer. We further showed that the non-coding LIN28A mRNA promotes the metastasis but not proliferation of colon cancer cells in vitro and in vivo. Mechanistically, we revealed that Methionyl aminopeptidase 2 (METAP2) is one of the up-regulated metastasis regulators upon over-expression of non-coding LIN28A identified by mass spectrum, and confirmed that it is non-coding LIN28A mRNA instead of LIN28A protein promotes the expression of METAP2. Moreover, we demonstrated that knockdown of DICER abolished the promotional effects of non-coding LIN28A on the metastasis and METAP2 expression. Conclusively, we showed that hypoxia induces the production of LIN28A mRNAs but segregated them into the P-bodies together with miRNAs targeting both LIN28A and METAP2, and then promotes the metastasis by positively regulating the expression of METAP2. This study uncovered a distinctive role of hypoxia in manipulating the metastasis and proliferation by differently regulating the expression of LIN28A at mRNA and protein level.